In silico identification and characterlization of the lectin gene families in cassava (Manihot esculenta Crantz) - Ha, Chu Duc; Wyckhuys, Kris A.G.; Dung, Le Tien (Academia Journal of Biology, 2017)
Plant lectins, a superfamily of glycan-binding proteins, play important roles in various biological processes, including plant defense and cell signaling. Until now, little or no research has been carried out on lectins in cassava (Manihot esculenta Crantz); a prime food, feed and bio-energy crop in the tropics to sub-tropics. In this study, we identified 5 homologous genes encoding class V chitinases (CRA) and 17 genes encoding hevein (Hvi) domains in total and annotated them in the cassava genome. The large size of MeCRA and MeHvi genes possibly resulted from tandem duplication events, directly linked to the expansion of CRA and hevein gene families. Phylogenetic analysis showed 3 distinct groups of hevein genes with their typical gene organization. The most common motif of gene structure of MeCRA family was recorded to be 2 exons/1 intron. Promoter analysis revealed that most of the members of lectin gene families are assumed to be responsive to light conditions and are expressed in specific for particular organs or plant tissues. The presence of hormonal- and/or stress-responsive elements in the promoter regions of all lectin genes indicated their involvement in the crop’s stress response and plant signaling. Since most members of CRA and hevein family were strongly expressed in various major tissues/organs, products of those lectin genes may play important roles in the development of cassava plants, especially in plant defense system. Citation: Chu Duc Ha, Wyckhuys K. A. G., Le Tien Dung, 2017. In silico identification and characterlization of the lectin gene families in cassava (Manihot esculenta Crantz). Tap chi Sinh hoc, 39(3): 320-332. DOI: 10.15625/0866-7160/v39n3.9185 *Corresponding author: research@letiendung.info; dung.tien.le@monsanto.com Received 25 January 2017, accepted 20 August 2017